Donor‐recipient body size mismatch has no impact on outcomes after deceased donor whole liver transplantation: Role of donor liver size measurement. Issue 6 (19th April 2021) - Kubal, Chandrashekhar A.; Mihaylov, Plamen; Fridell, Jonathan; Cabrales, Arianna; Nikumbh, Tejas; Timsina, Lava; Soma, Daiki; Ekser, Burcin; Mangus, Richard
Abstract: The role of donor‐recipient body size mismatch (DRSM) on outcomes after whole liver transplantation (LT) is not clearly defined. At our center, in presence of considerable DRSM, objective assessment of the donor liver by a radiology or intraoperative evaluation by procuring surgeon was incorporated. To evaluate the impact of DRSM on graft outcomes with this approach, adult deceased donor whole liver transplants between July 2001 and December 2017 at our center were studied. DRSM was considered when the donor‐recipient body surface area (BSA) ratio (DR‐BSAr) was either <0.69 or >1.25. There were 54 (3.2%) transplants with DR‐BSAr <0.69 and 61 (3.6%) with DR‐BSAr >1.25. One‐year graft survival was 85% vs. 89% vs. 89%; ( p  = .64) for transplants with DR‐BSArs of <0.69, 0.69–1.25, and >1.25, respectively. Early allograft dysfunction (EAD) (28% vs. 27% vs. 37%; p  = .07), post‐transplant coagulopathy, bilirubinemia, and renal function were also comparable. In conclusion, with the actual measurement of the donor liver and recipient abdominal cavity, significant DRSM did not have a negative impact on early and long‐term outcomes. Routine measurement of donor liver size by radiology may be incorporated in liver allocation to improve utilization.